Gedunin Mitigates Cutibacterium acnes-Induced Skin Inflammation by Inhibiting the NF-κB Pathway - Ju Kyoung Sim; Ye Ji Heo; Jin Hak Shin; Seon Sook Kim; Su Ryeon Seo (Pharmaceuticals)
Background/Objectives: Cutibacterium acnes (C. acnes), a bacterium residing in hair follicles, triggers acne by inducing monocyte-mediated inflammatory cytokine production. Gedunin, a limonoid derived from Azadirachta indica (commonly known as neem), is renowned for its antifungal, antimalarial, anticancer, anti-inflammatory, and neuroprotective effects. However, its role in mitigating C. acnes-induced skin inflammation remains unexplored. This study investigates the anti-inflammatory effects of gedunin on C. acnes-induced skin inflammation and elucidates the underlying mechanisms. Methods: The anti-inflammatory activity of gedunin was assessed using RAW 264.7 mouse macrophage cells and mouse bone-marrow-derived macrophages (BMDMs). Key inflammatory mediators, including interleukin-1β (IL-1β), tumor necrosis factor-α (TNF-α), inducible nitric oxide synthase (iNOS), cyclooxygenase-2 (COX-2), and interleukin-6 (IL-6), were evaluated. Mechanistic studies focused on the nuclear factor-kappa B (NF-κB) and mitogen-activated protein kinase (MAPK) signaling pathways, along with the NOD-like receptor pyrin domain-containing 3 (NLRP3) inflammasome. An in vivo acne model was employed to examine gedunin’s therapeutic efficacy. Results: Gedunin significantly reduced the expression of IL-1β, TNF-α, iNOS, COX-2, and IL-6 in RAW 264.7 cells. It inhibited NF-κB activation without affecting the MAPK pathways, including JNK/SAPK, ERK, and p38 MAPK. Gedunin also suppressed the activation of the NLRP3 inflammasome in BMDMs. In the mouse acne model, gedunin effectively alleviated C. acnes-induced inflammation, primarily by targeting NF-κB signaling. Conclusions: Gedunin demonstrates potential as a therapeutic agent for acne treatment by targeting key inflammatory pathways, particularly NF-κB signaling. This study highlights gedunin’s promise as an alternative approach to managing C. acnes-induced skin inflammation.